Peran Majelis Gereja dalam Meningkatkan Kesejahteraan Sosial Ekonomi Umat Kristen melalui Pelayanan Diakonia - Widya Ariyani; Greget Widhiati (Jurnal Filsafat dan Teologi Katolik, 2024)
Diaconal ministry is one form of church service that embodies the love of Christ in serving others. However, in practice, this ministry is often carried out in a charitable manner and has yet to fully address comprehensive and sustainable empowerment of the congregation. This study is driven by the urgent need to develop a diaconal service that not only provides temporary assistance but also effectively enhances the socio-economic independence of the congregation, particularly within the context of Gereja Isa Almasih Pringgading, where some Christian members face economic challenges due to limited access, resources, and institutional church support. The objective of this study is to analyze and describe the role of the Church Council in developing reformative and sustainable empowerment-based diaconal ministry. A qualitative descriptive method was employed, with data collected through in-depth interviews with Church Council members and service recipients, direct observations of diaconal activities, and documentation of church archives and social service reports. Data were analyzed thematically to identify patterns of service, empowerment strategies, and socio-economic impacts on the congregation. The study's findings reveal that the Church Council plays a strategic role in transforming diaconal ministry from mere charitable assistance into a structured empowerment program. Successfully implemented programs include entrepreneurial skills training, micro-business mentoring for congregation members, internal church cooperative development, and the establishment of local economic partnership networks. The impacts of these programs are reflected in increased household incomes, improved economic independence for some members, and strengthened social solidarity within the congregation. This study produces a conceptual model of empowerment-based diaconal ministry that can be replicated by other local churches to sustainably enhance congregational welfare.